Comprehensive Physiology 2011
DOI: 10.1002/cphy.c100002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Ventilation and Perfusion: Mechanisms and Regulation

Abstract: With increasing spatial resolution of regional ventilation and perfusion, it has become more apparent that ventilation and blood flow are quite heterogeneous in the lung. A number of mechanisms contribute to this regional variability, including hydrostatic gradients, pleural pressure gradients, lung compressibility, and the geometry of the airway and vascular trees. Despite this marked heterogeneity in both ventilation and perfusion, efficient gas exchange is possible through the close regional matching of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 119 publications
1
51
3
4
Order By: Relevance
“…These asymmetries grow in magnitude with each succeeding generation, resulting in heterogeneous distribution in ventilation and perfusion both in horizontal and vertical dimensions. 43 Of particular importance is that only 1-25% of pulmonary perfusion is mediated by gravitational forces compared with the influence of vascular architecture. 44 This has been referred to as the Slinky effect, 44 in which the lung is analogous to a deformable spring that distorts under its own weight (eg, more spring coils gather at the base of a vertically oriented spring).…”
Section: Ventilation/perfusion Relationshipmentioning
confidence: 99%
“…These asymmetries grow in magnitude with each succeeding generation, resulting in heterogeneous distribution in ventilation and perfusion both in horizontal and vertical dimensions. 43 Of particular importance is that only 1-25% of pulmonary perfusion is mediated by gravitational forces compared with the influence of vascular architecture. 44 This has been referred to as the Slinky effect, 44 in which the lung is analogous to a deformable spring that distorts under its own weight (eg, more spring coils gather at the base of a vertically oriented spring).…”
Section: Ventilation/perfusion Relationshipmentioning
confidence: 99%
“…In the healthy resting lung, V A/Q matching is thought to occur largely as a result of passive mechanisms, such as vascular branching structure and the effect of gravity (18). The effects of gravity are manifested as gradients in hydrostatic pressure (affecting blood flow), intrapleural pressure (affecting alveolar size and therefore ventilation) interacting to affect alveolar expansion, airway or blood vessel diameter, and local resistances, facilitating V A/Q matching.…”
Section: Effects Of Posturementioning
confidence: 99%
“…Although several mechanisms are thought to accomplish V A/Q matching in the healthy lung (see Ref. 18 for review), it is thought that passive mechanisms dominate under normal conditions. Such passive mechanisms include vascular branching structure and the effect of gravity on ventilation and perfusion (53).…”
mentioning
confidence: 99%
“…The latter mechanism was considered as true as intuitively it was thought that the change in gravity direction will affect the lung perfusion in the same way, i.e., less perfusion towards dorsal lung regions, now non-dependent, in the prone position. Several experiments found that the dorsal lung regions when in the prone position still had the highest amount of blood flowing through them (2)(3)(4)(5)(6)(7)(8). Therefore, this unexpected finding argued against the second mechanism to explain the reduction in intra-pulmonary shunt.…”
Section: Rationalementioning
confidence: 99%